2006
DOI: 10.1080/09593332708618719
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Organic Compounds (VOCs) Biofiltration with Two Packing Materials

Abstract: The treatment of a gas stream containing a mixture of acetone, toluene and trichlorethylene (TCE) was tested in two biofilters packed with compost only (biofilter B1) or a mixture of pozzolan and compost (biofilter B2). The biofilter performance was evaluated at VOCs concentration of 101 mg m(-3) of acetone - 210 mg m(-3) of toluene - 89 mg m(-3) of TCE and air flow of 0.8 m(3) h(-1). Inocula were provided by the compost native microflora and microbial growth was enhanced by periodically adding an average of 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…teršalams iš oro valyti taikomi įvairūs metodai (absorbcija, adsorbcija ir kt. ), tačiau dažniausiai iš jų pasirenkamas biologinis oro valymas (Gracy et al 2006;Skaistys, Vaiškūnaitė 2006;Vaiškūnaitė 2008;Ryu et al 2010).…”
Section: įVadasunclassified
“…teršalams iš oro valyti taikomi įvairūs metodai (absorbcija, adsorbcija ir kt. ), tačiau dažniausiai iš jų pasirenkamas biologinis oro valymas (Gracy et al 2006;Skaistys, Vaiškūnaitė 2006;Vaiškūnaitė 2008;Ryu et al 2010).…”
Section: įVadasunclassified
“…Since the biofiltration involves microorganism for degradation of pollutants, which suggest that the main factor for controlling these processes requires proper growth and support media for microorganism, many researchers have used synthetic and natural materials such as polyurethane foams, polyester foams, wood charcoal, activated carbon, compost, corncob, and yard waste for biofilteration [5,[20][21][22][23]. But due to biocompatibility and natural support, natural biofilter media have shown better results than synthetic media.…”
Section: Introductionmentioning
confidence: 99%
“…In more recent papers (Alvarez-Hornos et al, 2007;Dorado et al 2012a, b;Gracy et al, 2006;Hwang and Tang, 1997;Iliuta and Larachi, 2004;Jeong at al., 2006;Morgado et al, 2004;Wani et al, 1997) the reported removal efficiency for toluene or xylene reached 90% or more depending on the initial concentration and load of the pollutant, air residence time in biofilters and type of bed materials. High loads of toluene can be treated by a non-specific consortium in biofiltration (up to 1280 g m -3 h -1 in the first 25 cm of the biofilter).…”
Section: Cpeczasopismapanpl; Degruytercom/view/j/cpementioning
confidence: 99%
“…Following the experience of earlier investigations carried out by other authors the present experimental studies lasted 1 year (Choi and Oh, 2002;Dorado et al, 2010;Gracy et al, 2006;Jorio et al, 2009;Trusek-Holownia et al, 2012;Vaiškūnaitė et al, 2005Vaiškūnaitė et al, , 2008Vaiškūnaitė et al, , 2011.…”
Section: Investigation Proceduresmentioning
confidence: 99%
See 1 more Smart Citation